Scout Members Cardio Pulmonary Resuscitation (CPR) Skills in Lubuklinggau City after CPR Training - Wijaya, Sapondra; Susmini, Susmini; Dwi Ari Wibowo, Wahyu; Soewito, Bambang (Yayasan Rumah Ilmu Professor, 2025)
A sudden stop in heart function is called cardiac arrest, and if CPR is not administered right away, it can be life-threatening. CPR training and education are required to boost both the quantity and quality of bystander CPR. In this study, the impact of CPR training on the CPR skills of Lubuklinggau City scout members will be examined. A quasi-experimental design with a pre- and post-test methodology was implemented in this study. A CPR mannequin was utilized as a simulation instrument in CPR training. A purposive sampling technique was used to collect samples from seventy-two scout members. The PPNI CPR SOP checklist used to assess the subject's CPR performance. A paired t-test was used to analyze the data, and the results showed that CPR training significantly improved the skills of scout members (t = -49.343, p value = 0.0001). Based on the analysis and discussion results, it can be said that scout members' abilities to perform CPR are positively impacted by CPR training that uses the simulation method.